Journal of Applied Informatics and Technology (Editorial Note): Vol. 6 No. 2 (2024): July-December - Journal of Applied Informatics; Technology (Journal of Applied Informatics and Technology, 2024)
The Journal of Applied Informatics and Technology (JIT) has published research articles in its 6th volume, issue number 2 (2024), totaling eight articles. Of these, two are in English and six are in Thai. Each article has undergone peer review by at least three experts. The authors revised their articles according to the experts’ suggestions until the reviewers were accepted for publication. The editorial team has also proved the accuracy of each article’s content, references, and language usage to ensure the highest quality. The editorial team thanks all the experts for their valuable reviews and recommendations. The articles published in this volume include: Investigation of the Top Scopus-Indexed Journals in Agricultural and Biological sciences Across Diverse Asian Countries: A Bibliometric Analysis. Authors: Sattra Maporn, Jirarat Puseerit, Phakwilai Rungwisai, Panyawat Arsapar, Pichaya Chowtivannakul, Chonlatee Photong (Maporn et al., 2024) Thai Word Segmentation using a Replacing the English Alphabet Approach to Enhance Thai Text Sentiment Analysis. Authors: Vuttichai Vichianchai, Sumonta Kasemvilas (Vichianchai & Kasemvilas, 2024) Development of an Online Exhibition using Inquiry-Based Learning Management. Author: Siriporn Noiumkar (Noiumkar, 2024) Artificial Intelligence Model for Cooperative Organic Farming. Authors: Attapap Maneetoem, Siriwan Dangcham (Maneetoem & Dangcham, 2024) The Study of Sound Intensity Distribution and Its Relationship Overtime with the Livelihoods of People in the Community Around Samui Airport. Authors: Kodchagan Sri-ta, Kanokpim Thongyat, Supawadee Tosiri, Nutthapol Junkaew (Sri-ta et al., 2024) The Study Results of Perception and Satisfaction of Elementary School Students with 2D Animation Cartoon: Primal Hunter. Authors: Chalantorn Thaluang, Punyarat Rungsoongnern (Thaluang & Rungsoongnern, 2024) Online Marketing Communication Media Development of the Ban Wang Rang Yai Food Processing Community Enterprise to Add Value and Increase the Community Income at Makluea Kao Subdistrict, Sung Noen District, Nakhon Ratchasima Province. Author: Pheerawish Khamcharoen (Khamcharoen, 2024) The Development of Computer Inventory Management System for Faculty of Science and Technology Nakhon Ratchasima Rajabhat University. Author: Thamonwannapohn KhaKhum (Khakhum, 2024) The editorial board of the Journal of Applied Informatics and Technology (JIT) sincerely hopes that the eight articles published will be beneficial to researchers, providing knowledge that can be used to further develop their research in the future. Assoc. Prof. Olarik Surinta, Ph.D. Editor-in-Chief